2021
DOI: 10.3389/fchem.2021.705358
|View full text |Cite
|
Sign up to set email alerts
|

Steam Explosion Pretreatment of Lignocellulosic Biomass: A Mini-Review of Theorical and Experimental Approaches

Abstract: Steam Explosion (SE) is one of the most efficient and environmentally friendly processes for the pretreatment of lignocellulosic biomass. It is an important tool for the development of the biorefinery concept to mitigate the recalcitrance of biomass. However, the two distinct steps of SE, steam cracking and explosive decompression, leading to the breakdown of the lignocellulosic matrix have generally been studied in empiric ways and clarification are needed. This mini-review provides new insights and recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 45 publications
0
56
0
Order By: Relevance
“…This step promotes the hydrolysis of polysaccharides and lignocellulosic complex. The second stage of the process consists of a rapid depressurization causing water expansion and physical degradation of the LB (Jacquet et al, 2015;Ziegler-Devin et al, 2021). The combination of chemical and mechanical effects in SE treatment leads to a significant degradation and modification of the cell wall components, producing a cellulose-rich residue bearing a higher enzyme accessibility (Auxenfans et al, 2017;Sun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This step promotes the hydrolysis of polysaccharides and lignocellulosic complex. The second stage of the process consists of a rapid depressurization causing water expansion and physical degradation of the LB (Jacquet et al, 2015;Ziegler-Devin et al, 2021). The combination of chemical and mechanical effects in SE treatment leads to a significant degradation and modification of the cell wall components, producing a cellulose-rich residue bearing a higher enzyme accessibility (Auxenfans et al, 2017;Sun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Steam explosion (SE) is one of the most advanced, efficient and eco-friendly pre-treatment processes currently used for the production of biofuel from lignocellulose [ 60 ]. This process applied to hardwood lignin (Populus tremuloides) can yield up to 9.5% syringaldehyde, 4.7% vanillin and 0.4% 4-hydroxybenzaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…Steam explosion rendered the morphology to become patchy, broken, irregular, and melted, which subsequently would likely increase the specific surface area of the feedstuff. Such alterations in the structure might be interpreted as some components like hemicellulose are hydrolyzed or melted on the surface when the materials are cooked at high pressures and high temperatures, and the softened materials are torn out by the shear force of water steam when high pressure is sharply released at explosion ( 6 ). The decrease in FTIR peak intensity at 1,730 cm −1 , representing the carbonyl stretching, can be attributed to the acetyl, glucuronic acid, and ferulic ester groups of polysaccharides ( 24 , 25 ), which indicated that steam explosion processing resulted in serious cleavage of acetyl groups.…”
Section: Discussionmentioning
confidence: 99%
“…Many attempts have been made to intensify the utilization of such abundant feed resources. Among the alternatives, steam explosion processing sounds like a promising physicochemical pretreatment that effectively breaks up the lignocellulosic structure and alters hemicellulose and lignin contents by the effects of steam cooking on the duration and steam shear force at explosion ( 5 , 6 ). It has become a common pretreatment method to destroy biomass recalcitrance in biofuel and pulping production.…”
Section: Introductionmentioning
confidence: 99%